Efektivitas Kinerja Pegawai Terhadap Pengarsipan Berkas pada Dinas Perindustrian, Perdagangan, Energi dan Sumber Daya Mineral Provinsi Sumatera Utara - Nurul Isnaini Putri; Laylan Syafina (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
In a company or organization, archives are a very important source of information. However, not all companies can manage archives digitally well. The aim of this research is to analyze the effectiveness of employee performance in archiving files at the industry, trade, energy and mineral resources services of North Sumatra province based on qualitative research methods. The benefit of this research is to determine the level of employee performance when experiencing file archiving obstacles. If the archives owned by an organization are not well managed, the consequences will affect the level of reputation of an organization, so that the organization concerned will experience obstacles in achieving its goals.